Experimentos en el apoyo a partir de las apuestas de la Política Nacional de Humanizacion – Humaniza SUS - Martins, Catia Paranhos; Luzio, Cristina Amélia [UNESP] (FapUNIFESP (SciELO), 2014)
This paper seeks to narrate and reflect on some experimentation with institutional support, as proposed in the National Humanization Policy for Healthcare and Management – Humanize SUS of the Ministry of Health, Brazil. This support is taken as a method for questioning relationships, knowledge, practices and methods that have become naturalized within the daily-to-day activities of the Brazilian Health System. To this end, we present a brief contextualization of the Humanization Policy and then some situations of support are set as problems in order to indicate the challenges faced in the process of producing changes in healthcare and management within the Brazilian Health System.
Experimentações no apoio a partir das apostas da Política Nacional de Humanização - Humaniza SUS
Experimentation with support as proposed in the National Humanization Policy – “Humanize SUS”
Keywords: Brazilian health system; Humanization; Institutional support; National humanization policy